Influence Of E-Content Based Teaching on Selected Skills in Kabaddi - Sundar, V.; Yokesh, Dr.T.P. (South Eastern European Journal of Public Health, 2024)
To achieve the purpose of this study 30 male kabaddi players from Alagappa University College of Physical Education, Karaikudi were selected as subjects and their age ranged between 18 and 25 years. Group ‘A’ underwent teaching & coaching with e-content package and Group ‘B’ undergone no training. Experimental group undergone respective schedule for six weeks on alternate days. Teaching & coaching session in the field lasted for 60 minutes. The subjective rating was done by three qualified coaches on each skill selected in this study. The rating was done on 10 points scale by each coach and average on each skill was taken as individual score. Analysis of covariance, was used. It was also found that practicing skills with e-content package shown significant improvement than the control group.